MALAYSIAN EMPLOYMENT LAW AND INDUSTRIAL RELATIONS - Maimunah Aminuddin, 1949-, author 278722 (Kuala Lumpur : McGraw Hill Book, 1996)
Maimunah Aminuddin provides a clear and easy to understand insight into the various compenents of the Malaysian industrial relations system, including the role of government, trade unions, and employers. She examines the rights of employees to join and be active in a trade union, collective bargaining, trade disputes, industrial action and the Industrial Court. She also explores the employment laws which establish the basic rights for employees and employers, whether or not they belong to trade unions including the safety and health legislation. Employers rights to take disciplinary action are also described in detail. The book's concepts are illustrated with examples and relevant statistics. This book is an essential text for students of industrial relations, human resource practitioners and trade union leaders.